Industrial waste management : a case study of the tanning industry - Vichakorn Hengsadeekul; Nagarur, Nagendra N.; Zhuang, Ya-Hui; Shrestha, Ram M. (Bangkok : Asian Institute of Technology, 1991)
The purpose of this study is to find a process that is suitable for tanning industries to produce their products while maintaining quality, quantity and economic feasibility but at the same time reduce wastes or pollution. In achieving these objectives, the current study is organized as follows: Firstly, it tries to understand the causes in the tanning industry that create pollution. Secondly, it tries to find major stages of the process that create a large amount of pollution. Thirdly, it suggests modifications to the process for better pollution output, based on cost benefit analyses. In this study, the process for production is modified by two new processes. The modified processes that add pre-tanning and re-tanning stage can be used with all tannage and the pollution can be reduced. From the cost-benefit analysis, it is shown that the modified processes are feasible for implementation.
A thesis study submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1991
Keywords: Tanning -- Waste disposal; Factory and trade waste